Case report: Kinetics of viral load, immunoglobulins, and cytokines in a fatal case of Crimean-Congo hemorrhagic fever virus - Moufid Mhamadi; Moufid Mhamadi; Ousseynou Sene; Arfang Diamanka; Moundhir Mhamadi; Marie Pedapa Mendy; Andy Mahine Diouf; Mignane Ndiaye; Mamadou Aliou Barry; Samba Niang Sagne; Mahfouz Cissé Traoré; Amadou Alpha Sall; et al. (Frontiers in Virology)
A fatal case of Crimean-Congo hemorrhagic fever virus (CCHFV) was detected in Dakar, Senegal, West Africa, in April 2023. To elucidate the mechanisms involved in this outcome, the kinetics of viral load, immunoglobulins, and cytokines were assessed using RT-qPCR and ELISA. A high IL-6 titer, low IL-10 titer, and delayed IgG response were associated with disease severity. These biomarkers may serve as predictors of disease severity, potentially aiding in early intervention and treatment strategies.